Review of the Imaging Performance and the Current Status of the Cascade Gamma-Rays Coincidence Imagers - Nkuba, Leonid L.; Junior, Innocent J.; Mohamed, Salum M.; Lugendo, Innocent J.; Mohammed, Najat K. (Tanzania Journal of Engineering and Technology, 2023)
Various studies that have investigated the detection of gamma coincidence events have revealed that design factors and image reconstruction approaches dictate the spatial resolution, coincidence efficiency, and levels of statistical noise of the detection system. In the case of imaging, cascade gamma-ray coincidence (CGC) imagers coupled with collimated detectors offer promising values for both spatial resolution and coincidence efficiency. However, to date, no CGC imager with single or multiple collimated detectors has reported a performance level beyond 6.7 mm spatial resolution (FWHM) and 6.0 Ã—1ncidence efficiency. Given the recent developments and the current interests in high resolution and localization of an individual decaying nucleus, there is a need for CGC imagers with higher performance in terms of spatial resolution and efficiency. Therefore, deploying a CGC imager coupled with multiple collimated detectors may prove to be of value in nuclear imaging and probably in clinical applications Keywords: Cascade gamma-rays, Coincidence imager, Spatial resolution, Coincidence efficiency, and Signal to Noise ratio.